Exploring the impact of operational performance on smallholder agricultural cooperatives for sustainable community development at Elias Motsoaledi Municipality in Limpopo - Malapela, Ramadimetje Joyce (My University, 2021)
Cooperatives are recognised as an important instrument to reduce poverty, create employment, achieve economic growth and development. As a result, smallholder farmers with common interests have organised themselves and registered agricultural cooperatives. However, the operational performance of smallholder agricultural cooperatives for sustainable community development has remained poor. The purpose of the study is to explore the operational performance of smallholder agricultural cooperatives for sustainable community development in Elias Motsoaledi Local Municipality in Limpopo Province. Mixed research design was used in this study. Data was collected from sixty participants, questionnaires and semi-structured interviews were used to collect primary data for both quantitative and qualitative methods. The study found that smallholder agricultural cooperatives in the area of the study face challenges such as lack of managerial skills, poor governance, lack of adequate financial support and access to loans, lack of clarity on policy as well as lack of alternative strategies. The main findings of the study confirmed that there are challenges associated with the operational performance for sustainable community development. Inadequate financial support and lack of managerial skills were regarded as the main challenges that hinder the operational performance for sustainable community development. The study has suggested alternative strategies and recommendations that can assist smallholder agricultural cooperatives to improve their operational performance for sustainable community development.
Thesis (M.Dev. ( Planning and Management)) -- University of Limpopo, 2021
Keywords: Poverty; Economic growth; Operational performance; Agricultural cooperatives; Agriculture, Cooperative -- South Africa -- Limpopo; Community development -- South Africa -- Limpopo; Agriculture -- South Africa -- Limpopo